Reliability prediction of an offshore wind turbine gearbox - Bhardwaj, U.; Teixeira, A.P.; Soares, C. Guedes (Renewable energy, 2019)
This paper estimates the failure rate of an offshore wind turbine gearbox based on the data available for similar, known onshore wind turbine systems. The gearbox is one critical element of the wind turbine system and its failure may cause long downtime and consequently high operational and maintenance costs. First, a detailed Failure Mode and Effects Analysis is conducted and then the main Reliability Influencing Factors on the failure causes are identified. A reliability prediction method is then illustrated stepwise to estimate the total failure rate of an offshore wind turbine gearbox. Furthermore, a case study is used to demonstrate the importance of this technique for comparing the failure rate of subsequent components of onshore and offshore wind turbine gearbox. It is expected that the analysis conducted will help in understanding the field performance of offshore wind turbine gearbox in an offshore environment. Also, the approach adopted in this paper can be helpful to predict reliability for other wind turbine components. •This paper estimates the failure rate of an offshore wind turbine gearbox based on the data available for similar systems.•A detailed FMEA is conducted and then the main Reliability Influencing Factors on the failure causes are identified.•A reliability prediction method is then illustrated to estimate total failure rate of an offshore wind turbine gearbox.•A case study is used to demonstrate the importance of this technique.